Atypical Leydig Cell Hyperplasia in Adult Rats with Low T and High LH Induced by Prenatal Di(n-butyl) Phthalate Exposure. (April 2013) - Wakui, Shin; Takahashi, Hiroyuki; Mutou, Tomoko; Shirai, Masaru; Jutabha, Promsuk; Anzai, Naohiko; Wempe, Michael F.; Kansaku, Norio; Hano, Hiroshi; Inomata, Tomo; Endou, Hitoshi
The present study describes atypical Leydig cell (LC) hyperplasia in 20-week-old Sprague-Dawley rats with low testosterone and high luteinizing hormone levels after prenatal administration of 100 mg/kg/day di( n -butyl) phthalate on days 12 to 21 postconception. Light microscopy revealed LC hyperplasia surrounded by severely degenerated seminiferous tubules. Aggregated LCs had large ovoid nuclei with nucleoli and abundant eosinophilic cytoplasm. Immunohistochemical analysis showed expression of proliferating cell nuclear antigen and vimentin in many hyperplastic LCs. Electron microscopy revealed atypical nuclei, abundant free ribosomes, stripped rough endoplasmic reticulum, intermediate-size filaments, elongated cytoplasmic filopodia, atypical tight junctions, and cilia formations, but smooth endoplasmic reticulum was scarcely observed.